The mid-infrared - hard X-ray correlation in active galactic nuclei - Horst, Hannes (2008)
The cornerstone of the unified scenario for active galactic nuclei (AGN) is the existence of an obscuring torus. While the unified scenario has proven very successful, little is known about the physical state of the torus itself. In this work, we present high spatial resolution mid-infrared (MIR) imaging of 25 nearby AGN. We investigate the correlation between the rest frame 12.3 micron and absorption corrected 2-10 keV luminosities. Since the X-rays originate in the accretion disc and the MIR continuum is accretion disc radiation reprocessed in the torus, this enables us to constrain the torus geometry. We find a strong and highly significant correlation between both luminosities with L_MIR ~ L_X^(1.04 +- 0.04). Furthermore, we find that with a probability of 97 %, type I and type II AGN have the same luminosity ratio L_MIR / L_X. The high spatial resolution of our MIR imaging allows us to exclude any significant non-torus contribution to the AGN mid-IR continuum, thereby implying that the similarity in the L_MIR / L_X ratio between type Is and type IIs is intrinsic to AGN. We argue that this is best explained by clumpy torus models. The slope of the correlation is in good agreement with the expectations from the unified scenario and indicates little to no change of the torus geometry with luminosity. In addition, we demonstrate that the high angular resolution is crucial for AGN studies in the IR regime.
Keywords: Hochschulschrift; Harte Röntgenstrahlung; MIR; Aktiver galaktischer Kern